2016
DOI: 10.1177/0269216316634245
|View full text |Cite
|
Sign up to set email alerts
|

Lived experiences of parents caring for a child with a life-limiting condition in Australia: A qualitative study

Abstract: This study builds upon the growing body of evidence available in paediatric palliative care internationally. The key themes highlight the substantial demand for both physical and emotional support beyond what is currently offered and call for the implementation of carefully planned support services and other societal initiatives which seek to alleviate the broad health impacts to caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
160
0
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(177 citation statements)
references
References 33 publications
5
160
0
12
Order By: Relevance
“…The testimonies corroborate with Australian and Brazilian authors, who affirm that the diagnosis caused fear when they were faced with the disease. [9][10] When the diagnosis of the child's disease occurs during pregnancy or in the neonatal period, mothers may present feelings of guilt regarding the malformation, generating stress in a period of physiological and psychosocial changes, in which the mother's imagination lies in the perception of a "perfect"child, according to the following reports: [ It was noted that most of the caregivers were diagnosed with the child's diagnosis of CKD during pregnancy due to a congenital malformation of the urinary tract, which can cause the mother to feel guilty and carry the guilt for the rest of her life.…”
Section: Discovering the Diseasementioning
confidence: 99%
“…The testimonies corroborate with Australian and Brazilian authors, who affirm that the diagnosis caused fear when they were faced with the disease. [9][10] When the diagnosis of the child's disease occurs during pregnancy or in the neonatal period, mothers may present feelings of guilt regarding the malformation, generating stress in a period of physiological and psychosocial changes, in which the mother's imagination lies in the perception of a "perfect"child, according to the following reports: [ It was noted that most of the caregivers were diagnosed with the child's diagnosis of CKD during pregnancy due to a congenital malformation of the urinary tract, which can cause the mother to feel guilty and carry the guilt for the rest of her life.…”
Section: Discovering the Diseasementioning
confidence: 99%
“…This literature found that carers were often unprepared when finding themselves in situations where they must assist with activities of daily living, manage medication, and provide physical care and transportation, amongst other practical tasks (Funk et al, ; Stajduhar et al, ; Williams & McCorkle, ). The time commitment involved in providing end‐of‐life care had other practical challenges associated, such as an impaired ability to maintain existing social connections, employment, or recreational activities (Beng et al, ; Collins et al, ). Similarly, providing end‐of‐life care had significant financial impacts for some carers (Lewis, ; Stajduhar et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Carers were found to experience burnout as a result of their practical caring responsibilities, and also related to grieving processes as care recipients declined in health (Beng et al, 2013). Increased levels of anxiety, depression, and psychological distress were also reported amongst end-of-life carers, to the extent that negative psychological outcomes could be more significant amongst carers than their dying family members or friends (Beng et al, 2013;Collins et al, 2016;Linderholm & Friedrichsen, 2010;Melin-Johansson, Henoch, Strang, & Browall, 2012;Stajduhar et al, 2010;Totman et al, 2015;Williams & McCorkle, 2011). Those who cared for a dying family member at home were also found to be at risk of experiencing significant loneliness and isolation.…”
Section: Emotional Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…For respite ("short break" care), or end-of-life care, some families wish to be in a hospice or other homelike environment where there is more constant support from healthcare professionals (Collins et al, 2016;Smith, Graham, & Herbert, 2016). One recent study by Lindley, Colman, and Meadows (2017) found that intellectual disability in children was negatively related to hospice enrolment/utilization and length of stay, although more common when children had additional comorbidities.…”
Section: The Role Of Local Communities In Paediatric Palliative Carementioning
confidence: 99%